Identification, isolation, and structural characterization of novel forced degradation products of apixaban using advanced analytical techniques. Issue 21 (12th September 2022) - Salakolusu, Suresh; Sharma, Ganapavarapu Veera Raghava; Katari, Naresh Kumar; Puppala, Umamaheshwar; Kaliyapermal, Muralidharan; Vijay, Rajani; Doddipalla, Raju; Geereddi, Mahesh Kumar Reddy
Abstract : The current research explains the stress degradation behavior of Apixaban, which is an anticoagulant or blood thinner. The degradation was conducted using hydrolytic, oxidative, thermal, and photolytic conditions. Apixaban is relatively stable in oxidative, thermal, and photolytic conditions; however, considerable degradation was observed in acid and base hydrolysis. Degradation products were identified using ultra‐high performance liquid chromatography‐mass spectrometry, isolated using semi‐preparative high‐performance liquid chromatography, and structural characterization by high‐resolution mass spectrometry and nuclear magnetic resonance spectroscopy. A total of five degradation products were identified and isolated in acid and base degradation. Degradation products 1, 2, and 3 were observed in acid conditions, whereas in base conditions, along with those three, two more degradation products 4 and 5 were identified. The representative thing was that among the five degradation products, two sets of positional isomers 1, 4, and 2, 5 were observed; out of which 2 and 5 are novel. The remaining degradation products 1, 3, and 4 are already reported tentatively using a single analytical technique of mass analysis without any evidence from nuclear magnetic resonance spectroscopy. Hence, the present study focused on using high‐resolution mass, and nuclear magnetic resonance spectroscopy data for concrete confirmation of structures for degradation products.